Secular increase in the prevalence of gestational diabetes and its associated adverse pregnancy outcomes from 2014 to 2021 in Hebei province, China - Tian, Mei-Ling; Du, Li-Yan; Ma, Guo-Juan; Zhang, Ting; Ma, Xu-Yuan; Zhang, Ying-Kui; Tang, Zeng-Jun (Frontiers in Endocrinology, 2022)
Objective: we aimed to assess whether the frequency of adverse pregnancy outcomes among pregnancy women in Hebei province China with gestational diabetes mellitus changed. Methods：We analyzed the data from the monitoring information management system for pregnant women in 22 hospitals of Hebei Province China. 366,212 individuals with singleton live births from 2014 to 2021 were included in the study, of which 25,995 were diagnosed with gestational diabetes. We analyzed the clinical characteristics and the relationship between GDM and adverse pregnancy outcomes. Results：The average incidence of GDM was7.64%（25995/366212）. The incidence rate of GDM significantly increased from 2014 to 2021(χ2trend=7140.663, P＜0.001). The demographic and obstetric difference between the two groups was statistically significant in terms of maternal age, gravidity, parity, education level, and the incidence of pregnancy complications (gestational hypertension, heart diseases, and anemia) (P＜0.05). GDM individuals were at significantly increased risk of most assessed adverse pregnancy outcomes, including premature delivery cesarean delivery, uterine inertia, NICU admission，Apgar score at 1 min，and macrosomia (P＜0.05) . The multivariate logistic regression analysis showed that GDM was an independent risk factor in terms of premature birth, caesarean delivery, uterine inertia, placental abruption, NICU admission, and macrosomia. Conclusion：Women diagnosed with GDM are at risk for adverse outcomes, and require targeted approaches to therapy.